ANALISIS DESAIN KOMUNIKASI DALAM WAYANG SEBAGAI MEDIA PEMBELAJARAN DALAM PENDIDIKAN MULTIKULTURAL - yunita, gesnida (JURNAL Dasarrupa: Desain dan Seni Rupa, 2025)
This study aims to analyze communication design in wayang as a learning medium in multicultural education. Wayang,as one of Indonesia's cultural heritages,has great potential to be used as an educational tool that teaches the values ​​of multiculturalism. In the context of education, wayang not only functions as a means of entertainment, but also as an effective medium to convey diverse moral, social, and cultural messages.This study uses a case study method with a focus on the analysis of communication design elements contained in wayang performances, such as narratives, visuals, characters, and interactions with the audience.Data were obtained through observations of wayang performances, interviews with puppeteers and education experts,and analysis of related literature. In addition,this study also explores how wayang can be integrated into the education curriculum to strengthen students' understanding of cultural diversity, tolerance,and social harmony. The results of the study indicate that communication design in wayang has flexible and adaptive characteristics, so that it can be adjusted to different learning contexts. Wayang displays rich and diverse cultural symbols, which can introduce students to the plurality of identities and traditions in Indonesia. In addition, the interaction between the puppeteer and the audience allows for dynamic and participatory dialogue, which is important in the process of multicultural education.The conclusion of this study is that wayang has great potential as a learning medium that supports multicultural education.Therefore, the integration of wayang in formal and informal learning can be an effective strategy in enriching students' learning experiences in the context of multicultural education.